2014
DOI: 10.4236/aim.2014.413107
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Iron Availability on <i>Bacillus amyloliquefaciens</i> Growth

Abstract: Bacillus amyloliquefaciens is a biocontrol agent whose genome has been sequenced. Within the genome of B. amyloliquefaciens are genes associated with iron chelation, but these genes are not found within all sequenced strains. The impact of iron availability on the B. amyloliquefaciens physiology was examined in this study. B. amyloliquefaciens ATCC 23843 was cultured under ironreplete and iron-deplete conditions for 48 hours, at 37˚C. Final growth yields were dependent on iron concentration. Cultures grown in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…In the FeCl 3 test, the spectral analyses of Bacillus MAP3 ferrated siderophores, show a maximum absorbance at 495,which confirm the catecolate nature of the siderophores (Fig. 4-I), this result was consonance with a previous study (Clark et al, 2014), that indicated the predominate of catecholate type siderophores in the Bacillus genus, specifically Bacillibactin catecolate type siderophores. However, in the study of (Murugappan et al, 2011) they reported that its impossible to characterize the siderophores based on the bacteria species, because siderophores of varying nature have been produced by the same genus.…”
Section: Resultssupporting
confidence: 89%
“…In the FeCl 3 test, the spectral analyses of Bacillus MAP3 ferrated siderophores, show a maximum absorbance at 495,which confirm the catecolate nature of the siderophores (Fig. 4-I), this result was consonance with a previous study (Clark et al, 2014), that indicated the predominate of catecholate type siderophores in the Bacillus genus, specifically Bacillibactin catecolate type siderophores. However, in the study of (Murugappan et al, 2011) they reported that its impossible to characterize the siderophores based on the bacteria species, because siderophores of varying nature have been produced by the same genus.…”
Section: Resultssupporting
confidence: 89%